The Moderating Role of Employment in an Environmental Kuznets Curve Framework Revisited in G7 Countries - Bright Akwasi Gyamfi; Murad A. Bein; Ilhan Ozturk; Festus Victor Bekun (Indonesian Journal of Sustainability Accounting and Management, 2020)
Anthropogenic activities have resulted in environmental concerns due to the global consciousness for mitigating climate change issues. This awareness is emphasized in the sustainable development goals contained in the seventh and 13th targets. The study investigates the nexus between energy and growth while considering the moderating role of employment and its interaction with energy consumption in G7 countries for the period of 1980–2018. To achieve this objective, a carbon-income function is fitted to ameliorate the problems related to omitted variable bias. Empirical results indicate that all outlined variables are cointegrated over the investigated period, as reported by the Kao cointegration test. The study further validates the environmental Kuznets curve (EKC) hypothesis in the short-run. With emphasis on economic growth relative to environmental quality while in the long run, there is no statistical evidence in support of the EKC phenomenon. Furthermore, a 1% increase in energy consumption increases pollutant emission in the long run by 3.80%. Similarly, a positive elastic relationship is observed between trade and environmental degradation. This outcome is demonstrated in the causality results, which reveal a one-way causality running from trade to pollutant emission. These findings provide insights that can help policy formulations, including decoupling economic growth from pollutant emission and the need to adopt cleaner and eco-friendly technologies.